A Study on Evolution and Declination of Mughal Empire: The Rise and Fall of the Mughal Empire (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The Mughal Empire was founded by Babur, a CentralAsian ruler who was descended from the Turko-Mongol conqueror Timur on hisfather's side and fromChagatai, the second son of the Mongol ruler GenghisKhan, on his mother's side. Ousted from his ancestral domains inCentral Asia, Babur turned to India to satisfy his ambitions. He establishedhimself inKabul andthen pushed steadily southward into India from Afghanistan throughthe KhyberPass. Babur's forces occupied much of northern India after his victoryat Panipat in 1526. Thepreoccupation with wars and military campaigns, however, did not allow the newemperor to consolidate the gains he had made in India.[35] Theinstability of the empire became evident under his son, Humayun, who wasdriven out of India and into Persia by rebels. Humayun's exile in Persiaestablished diplomatic ties between the Safavid andMughal Courts, and led to increasing Persian cultural influence in the MughalEmpire. The restoration of Mughal rule began after Humayun's triumphant returnfrom Persia in 1555, but he died from a fatal accident shortlyafterwards. Humayun's son, Akbar, succeeded tothe throne under a regent, Bairam Khan,who helped consolidate the Mughal Empire in India.